Dissolution of olivines from steel and copper slags in basic solution. (July 2020) - Traynor, Brian; Mulcahy, Ciara; Uvegi, Hugo; Aytas, Tunahan; Chanut, Nicolas; Olivetti, Elsa A.
Abstract: This study explores the effect of aqueous chemical environment on the dissolution rate of the minerals γ-C2 S and fayalite, identified as primary phases of ladle furnace steel slag and copper slag. γ-C2 S and fayalite were exposed to solutions of NaOH and Ca(OH)2, chosen to mimic the pore solutions of alkali-activated and Portland-cement based binders. While both from the olivine mineral group, γ-C2 S and fayalite displayed opposing dissolution trends with respect to pH. The rates of γ-C2 S dissolution were observed to decrease with higher pH, while fayalite dissolution rates increased with pH, and both relationships were described via empirical functions of the form R  =  k  ∙  a H + n . The contrasting dependence of dissolution rate on pH for both minerals was attributed to the formation of chemically distinct surface layers on both minerals during dissolution. These results have significance for blending of slags with high olivine contents in binders with a range of aqueous chemical environments.